Resources and Incentives to Reform : A Model and Some Evidence on Sub-Saharan African Countries - De Blasio, Guido (IMF Working Papers; Working Paper ;, 2001)
The paper models the incentives for a self-interested government to implement "good policies". While good policies lead to investment and growth, they reduce the government's ability to increase supporters' consumption. The model predicts that resource abundance is conductive to poor policies and, consequently, to low investment. The implications of the model are broadly supported by evidence on sub-Saharan African countries. In particular, countries that are rich in natural resources tend to have lower institutional quality and worse macroeconomic and trade policies.